A three-dimensional TiO2-Ag / AgCl composite material and its preparation method and application

By assembling TiO2 nanostructures and AgCl crystals in situ on the Ag foil substrate, a three-dimensional TiO2-Ag/AgCl composite material was prepared, which solved the problems of complex preparation process, high cost and unstable SERS activity in the existing SERS substrate, and achieved Efficient and stable SERS detection effect.

CN118883528BActive Publication Date: 2025-02-21ZHEJIANG LAB
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411353987.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-21
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing SERS substrate has many steps, harsh conditions, complex processes, high costs, low reuse rates, and unstable SERS activity in indoor light and air environments.

Method used

Using Ag foil as the substrate, the TiO2 nanostructure unit and AgCl crystal are synchronously assembled through in-situ hydrothermal reactions of titanium isopropoxide, hydrochloric acid and ethylene glycol. After photoreduction and thermal migration treatment, three-dimensional TiO2-Ag/ AgCl composite material.

Benefits of technology

It realizes the efficient and stable preparation of three-dimensional TiO2-Ag/AgCl composite material, has good SERS activity and long-term effectiveness, and can maintain detection capabilities for a long time in indoor environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118883528B_ABST
    Figure CN118883528B_ABST
Patent Text Reader

Abstract

The invention discloses a three-dimensional TiO2-Ag / AgCl composite material and a preparation method and application thereof, belonging to the field of functional materials and Raman spectroscopy detection, and the preparation method comprises: (1) adding titanium isopropoxide to a mixture of ethylene glycol, concentrated hydrochloric acid and water, stirring, and then immersing Ag foil therein, and performing a hydrothermal reaction to prepare a substrate; (2) placing the substrate under a xenon light source, controlling the light source current to irradiate the substrate, so that part of the AgCl component in the substrate undergoes photoreduction to generate active single substance Ag; (3) placing the substrate after light treatment in a protective atmosphere, controlling the heating temperature at 200-500°C, so that the active single substance Ag undergoes thermal migration relying on TiO2 monomer, and preparing a three-dimensional TiO2-Ag / AgCl composite material. The composite material has good structural stability and adjustable structure, and the SERS activity is efficient and stable, and can be used for high-sensitivity detection of water pollutants such as antibiotics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional materials and Raman spectrum detection, and in particular to a three-dimensional TiO2-Ag / AgCl composite material and a preparation method and application thereof. Background Art

[0002] Detecting extremely low concentrations of carcinogenic mutagens, early disease markers, antibiotics, various pesticide residues, industrial pollutants and other trace molecules from complex systems is an important topic in the field of modern analytical chemistry and biotechnology, and is also one of the key technologies to ensure food safety, public health and drug development. Raman spectroscopy is a fingerprint-like, inelastic scattering spectrum with molecular structure specificity. Surface-enhanced Raman technology (SERS), which has gradually developed based on Raman spectroscopy, does not require any external markers and can highly sensitively identify molecules by utilizing the special vibration characteristics of metal nanostructures. It has shown great potential and value in many fields such as materials science, biomedicine, and environmental monitoring. However, SERS technology still faces some challenges: (1) The heterogeneity of the analyte signal is uncontrollable; (2) The reproducibility of low-concentration analyte signals is not high. To address this problem, researchers have obtained a variety of complex SERS substrates or structures through various assembly techniques, such as substrate structures assembled from basic units such as zero-dimensional nanoparticles, one-dimensional nanowires, nanorods, two-dimensional nanosheets, nanodisks, nanoporous structures, and multi-level structures. The above structures all exhibit their unique Raman scattering properties, but this type of structure has many assembly steps, harsh preparation conditions, complex processes, high costs, low reuse rates, and is far from practical applications.

[0003] Developing simple, efficient and stable material preparation, processing and assembly methods is one of the important contents of developing efficient SERS substrates. TiO2 is a semiconductor material that is inexpensive, bio-friendly, easy to process and of great practical value. Its rich surface binding sites provide innate chemical advantages for material complexes and detection and identification of target molecules. Its relatively wide energy gap structure and adjustability provide convenience for matching the special energy levels of the molecules to be detected and satisfying the relevant charge transfer resonances. Precious metals (such as Au, Pt, etc.) can induce electric fields in SERS applications and significantly improve the detection limit of the molecules to be detected due to their unique local surface resonance (LSPR) effect. They are widely used as SERS active components or sites in many SERS substrates. However, in practical applications, it is usually necessary to consider the stability of precious metal nano-active units to temperature, light, acidity and alkalinity, and air to ensure that the entire SERS substrate has continuous detection activity and stability. Therefore, in order to improve the performance of TiO2 SERS substrate, in addition to improving the binding and electronic interactivity of the overall structure of the material to the molecules to be tested, it is also necessary to select suitable metal active ingredients to enable various components to be appropriately coupled with each other in a simple way, so as to meet the requirements of structural stability and adjustability, and maintain the SERS activity of the substrate in indoor light and air environment for a long time.

[0004] The Chinese patent document with publication number CN105372223A discloses a flexible and reusable SERS substrate of Ag / TiO2 and a preparation method thereof. The invention uses a thin Ti sheet as a Ti source, prepares a TiO2 nanobelt array based on Ti by a hydrothermal synthesis method, and prepares the Ag / TiO2 SERS substrate material by a continuous ion deposition method; the Chinese patent document with publication number CN113670893A discloses a surface enhanced Raman scattering substrate and a preparation method and application thereof. The method first uses a hydrothermal method to place a titanium foil in a reactor containing a mixed solution of NaOH and urea to react, and prepares a TiO2 nanocone array of different morphologies by controlling the urea content; the TiO2 nanocone array is plated with Ag by a magnetron sputtering method to obtain an Ag / TiO2 substrate. The Ag / TiO2 substrate can be used to detect SARS-CoV-2S1 protein. However, the magnetron sputtering technology has high cost, complex equipment, and gas discharge and other undesirable phenomena may occur, affecting the deposition quality. Summary of the invention

[0005] In order to address the deficiencies of the prior art, the present invention provides a three-dimensional TiO2-Ag / AgCl composite material and a preparation method thereof, which has good structural stability and adjustable structure, a simple and efficient preparation method, relatively mild conditions, efficient and stable SERS activity, and can be used for high-sensitivity detection of water pollutants such as antibiotics.

[0006] The specific technical solutions adopted are as follows:

[0007] A method for preparing a three-dimensional TiO2-Ag / AgCl composite material comprises the following steps:

[0008] (1) adding titanium isopropoxide to a mixture of ethylene glycol, concentrated hydrochloric acid and water, stirring, and then immersing the washed and dried Ag foil therein, reacting at a heating environment of 80 to 150° C. for 1.5 to 7.5 h to prepare a substrate Ag-based TiO2-AgCl;

[0009] (2) placing the Ag-based TiO2-AgCl substrate under a xenon lamp light source, controlling the light source current to irradiate the substrate, so that part of the AgCl component in the substrate undergoes photoreduction to generate active elemental Ag;

[0010] (3) Placing the light-treated substrate in a protective atmosphere, controlling the heating temperature at 200-500°C, allowing the active single substance Ag to thermally migrate with the TiO2 monomer to prepare a three-dimensional TiO2-Ag / AgCl composite material.

[0011] The invention uses Ag foil as a base material, introduces an appropriate amount of concentrated hydrochloric acid, and controls the chlorination rate of the Ag foil surface and the hydrolysis rate of titanium isopropoxide at the same time, so that the in-situ deposition of TiO2 nanostructure units and the in-situ evolution of AgCl crystals on the Ag foil surface are coordinated, and finally a layer of disordered TiO2 nano-needle-shaped "lawn" is "planted" on the Ag base; the evolution and propagation rate of the AgCl crystal layer is relatively fast, and when the TiO2 nanostructure monomer is deposited on the Ag foil surface to "occupy a place", it will be squeezed by the rapidly spreading AgCl crystal layer "soil", so that the TiO2 monomer is finally firmly "planted" on the Ag base. The AgCl crystal layer is sensitive to light. Through light, many active Ag(0) can be generated on its surface, and these active Ag(0) can migrate on the nearby compatible TiO2 crystal plane under heating conditions. Therefore, the crystallinity of the TiO2 nanostructure can be regulated by controlling the heat treatment atmosphere, temperature and time, and the distribution of Ag(0) nanoparticles on the TiO2 nanounit can be controlled at the same time to prepare a three-dimensional TiO2-Ag / AgCl composite material.

[0012] Optionally, the thickness of the Ag foil is 0.005 to 2.0 mm, the purity is 99.00% to 99.998%, and the area is 0.5 cm×1.0 cm to 4.0 cm×8.0 cm; the Ag foil is immersed in 0.01 to 0.5 mol / L HNO3 solution, isopropanol, acetone, ethanol, and deionized water in turn for ultrasonic washing for more than 30 min, and then taken out and blown dry with high-purity nitrogen to obtain the washed and dried Ag foil for use.

[0013] Preferably, in the mixed solution in step (1), the volume ratio of ethylene glycol, concentrated hydrochloric acid and water is 0.2-1:0.2-1:1; and the amount of titanium isopropoxide added is 1-5 v / v% based on the volume of water in the mixed solution.

[0014] Optionally, the Ag-based TiO2-AgCl substrate is washed multiple times with isopropanol, acetone, ethanol, and deionized water for standby use.

[0015] Specifically, in step (2), the wavelength of the xenon lamp light source is 300 nm ≤ λ ≤ 1100 nm, the xenon lamp light source exit window is 5.0 to 50 cm away from the substrate, and the light source current is controlled so that the irradiation intensity received by the substrate is 10.0 to 200 mW / cm 2 The irradiation time is controlled between 2.0 and 30 min. AgCl has photosensitivity. By controlling the light source current irradiation, the surface of the AgCl component in the substrate can be photoreduced to generate active Ag(0).

[0016] Optionally, in step (3), the protective atmosphere is a nitrogen atmosphere or a nitrogen-hydrogen mixed atmosphere, and the heating time is 30 to 120 min. The three-dimensional structure of the Ag-based TiO2-AgCl substrate is not destroyed in the protective atmosphere at ~500°C, and the Ag(0) nanoparticles are thermally migrated from the substrate along the TiO2 nanoneedles to prepare a three-dimensional TiO2-Ag / AgCl composite material with adjustable structure and properties.

[0017] The invention also provides a three-dimensional TiO2-Ag / AgCl composite material prepared by the preparation method of the three-dimensional TiO2-Ag / AgCl composite material.

[0018] In the three-dimensional TiO2-Ag / AgCl composite material, TiO2 nanoneedles are in-situ assembled on an Ag foil substrate based on the inlay effect of AgCl, the TiO2 nanoneedles form a lawn-like three-dimensional structure, and Ag nanoparticles are randomly distributed on the TiO2 nanoneedles; the length of the TiO2 nanoneedles is 0.1 to 1 μm, the diameter is 10 to 60 nm, the particle size of the Ag nanoparticles is 5 to 40 nm, and the Ag nanoparticles are highly dispersed and not agglomerated.

[0019] The present invention also provides application of the three-dimensional TiO2-Ag / AgCl composite material in surface enhanced Raman scattering detection.

[0020] The present invention also provides a method for detecting antibiotics in an aqueous solution, using the three-dimensional TiO2-Ag / AgCl composite material. Specifically, the three-dimensional TiO2-Ag / AgCl composite material is contacted with the aqueous solution to be tested, and Raman spectroscopy is performed after drying.

[0021] Optionally, the antibiotic is a quinolone antibiotic such as norfloxacin, norfloxacin, ofloxacin, ciprofloxacin, and fleroxacin.

[0022] Experiments have shown that the three-dimensional TiO2-Ag / AgCl composite material can stably detect concentrations below 10 - 6 mol / L norfloxacin solution, the detection limit can reach 10 -10 mol / L, and the three-dimensional TiO2-Ag / AgCl composite material has long-lasting SERS activity.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention provides an in-situ preparation method of a three-dimensional TiO2-Ag / AgCl composite material, wherein Ag foil is selected as a source material of a substrate, and TiO2 nanostructure units are synchronously assembled onto the surface of the Ag foil by means of a chlorination process on the surface of the Ag foil through an in-situ hydrothermal reaction with titanium isopropoxide, hydrochloric acid and ethylene glycol. The AgCl component in the composite structure serves as a photosensitizer, and provides an active Ag(0) migration source for the composite structure through photoreduction. The composite structure is then subjected to a heat treatment in an inert gas or 5% reducing atmosphere, and finally a three-dimensional TiO2-Ag / AgCl composite material is obtained. In the three-dimensional TiO2-Ag / AgCl composite material, TiO2 nanoneedles are in-situ assembled on the Ag foil substrate based on the embedding effect of AgCl, and the TiO2 nanoneedles form a lawn-like three-dimensional structure, and Ag nanoparticles are randomly distributed on the TiO2 nanoneedles.

[0025] (2) The continuous in-situ assembly and processing method of the method of the present invention expands the composite form between materials with mismatched lattices and expands the application scope of the material; the functional material components of the structure are distributed more randomly and evenly, and the nanostructure is conducive to the increase of specific surface area; the TiO2 nanoneedle units are squeezed by the AgCl crystal layer on the substrate surface, so that each TiO2 nanoneedle "lawn" structure can be firmly "planted" on the Ag substrate and has structural stability; the heterogeneous interface and SERS performance of the three-dimensional TiO2-Ag / AgCl composite material structure have high stability and can maintain SERS activity for a long time in indoor light, temperature and air environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a SEM image of the three-dimensional TiO2-Ag / AgCl composite material prepared in Example 1, with a scale of 40 μm.

[0027] Figure 2 This is a SEM image of the three-dimensional TiO2-Ag / AgCl composite material prepared in Example 1, with a scale of 100 nm.

[0028] Figure 3 This is the process XRD pattern of the three-dimensional TiO2-Ag / AgCl composite material prepared in Example 1.

[0029] Figure 4 This is a SEM image of the three-dimensional TiO2-Ag / AgCl composite material prepared in Example 2, with a scale of 100 μm.

[0030] Figure 5 This is the SEM image of the three-dimensional TiO2-Ag / AgCl composite material prepared in Example 2, with a scale of 200 nm.

[0031] Figure 6 This is the process XRD pattern of the three-dimensional TiO2-Ag / AgCl composite material prepared in Example 2.

[0032] Figure 7 This is a SEM image of the three-dimensional TiO2-Ag / AgCl composite material prepared in Example 3, with a scale of 15 μm.

[0033] Figure 8 This is a SEM image of the three-dimensional TiO2-Ag / AgCl composite material prepared in Example 3, with a scale of 2 μm.

[0034] Fig. 9 This is the process XRD pattern of the three-dimensional TiO2-Ag / AgCl composite material prepared in Example 3.

[0035] Fig.10 The three-dimensional TiO2-Ag / AgCl composite material prepared in Example 1 is 10 -4 ~10 -10 SERS detection spectrum of mol / L norfloxacin solution.

[0036] Fig.11 The three-dimensional TiO2-Ag / AgCl composite material prepared in Example 1 was continuously treated for 10 days. -6 Comparative graph of SERS detection stability of 1 mol / L norfloxacin solution. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with the examples and drawings. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. Contents not described in detail in this specification belong to prior art known to professionals and technicians in the field.

[0038] In the embodiment, the flat Ag foil used has a thickness of 0.005-2.0 mm and a purity of 99.00%-99.998%. It is cut into foil sheets with an area of ​​0.5 cm×1.0 cm~4.0 cm×8.0 cm, and is successively immersed in 0.1-1 mol / L HNO3 solution, isopropanol, acetone, ethanol, and deionized water for ultrasonic washing for more than 30 min, taken out and blown dry with high-purity nitrogen for later use.

[0039] Example 1

[0040] Step 1: In-situ assembly of Ag-based TiO2-AgCl substrate;

[0041] Add 2 ml of concentrated hydrochloric acid to 10 ml of deionized water and stir thoroughly; then add 4 ml of ethylene glycol and mix thoroughly to obtain a mixed solution; slowly add titanium isopropoxide dropwise in a volume of 0.2 ml and stir thoroughly to mix; immerse the cleaned and dried Ag foil that has been ultrasonically washed in dilute nitric acid, isopropanol, acetone, ethanol, and deionized water in the above solution, seal it, and then perform a hydrothermal reaction at 120°C, and control the reaction time to 2.5 h to prepare a substrate Ag-based TiO2-AgCl, and wash the substrate with isopropanol, acetone, ethanol, and deionized water for multiple times for use.

[0042] Step 2: Photoinduced generation of active elemental Ag on the AgCl surface;

[0043] The prepared Ag-based TiO2-AgCl substrate was placed horizontally under a xenon lamp light source (300nm ≤ λ ≤ 1100 nm), with the light source exit window 30 cm away from the substrate sample. The light control mode of the light source was used to control the light source current so that the irradiation intensity received by the substrate sample was 100 mW / cm 2 The irradiation time was 5 min. The photosensitivity of AgCl was utilized to photoreduced the surface of the AgCl component in the composite structure to generate active single substance Ag. The obtained sample was stored dry at room temperature for later use.

[0044] Step 3: Active single substance Ag forms Ag particles distributed on the TiO2 structural monomer through thermal migration;

[0045] The Ag-based TiO2-AgCl composite structure treated with light was placed in a tubular furnace in a nitrogen atmosphere, and the heating temperature was controlled at 300°C for 60 min, so that the active Ag on the surface of AgCl could be thermally migrated by relying on the TiO2 nano-monomer, and stable Ag nano-particles were randomly distributed in batches on the TiO2 monomer, and finally a three-dimensional TiO2-Ag / AgCl composite material was prepared. The SEM image of the three-dimensional TiO2-Ag / AgCl composite material is shown in FIG. Figure 1 and Figure 2As shown in FIG. 1 , the length of the TiO2 nanoneedles is about 200 to 300 nm, the diameter is about 20 to 50 nm, and the particle size of the Ag nanoparticles is about 5 to 20 nm. The XRD characterization of the three-dimensional TiO2-Ag / AgCl composite material is shown in FIG. Figure 3 As shown, the diffraction pattern shows typical diffraction peaks of rutile phase TiO2, cubic AgCl and Ag crystals, without any other impurity phase signals.

[0046] Example 2

[0047] The difference between this embodiment and embodiment 1 is that: in step 1, the addition of 10 ml of deionized water is changed to the addition of 7 ml of deionized water, and the addition of 4 ml of ethylene glycol can be changed to the addition of 7 ml of ethylene glycol. The other parameters and processes are the same as those in embodiment 1, and a three-dimensional TiO2-Ag / AgCl composite material is prepared, wherein the aspect ratio of the TiO2 monomer structure is different from that in embodiment 1; the SEM image of the three-dimensional TiO2-Ag / AgCl composite material is shown in FIG. Figure 4 and Figure 5 As shown, the length of the TiO2 nanoneedles is about 0.8 to 1 μm, the diameter is about 50 to 60 nm, and the particle size of the Ag nanoparticles is about 10 to 30 nm. The XRD characterization of the process is as follows Figure 6 As shown, the diffraction pattern shows typical diffraction peaks of rutile phase TiO2, cubic AgCl and Ag crystals, without any other impurity phase signals.

[0048] Example 3

[0049] The difference between this embodiment and embodiment 1 is that in step 1, adding 2 ml of concentrated hydrochloric acid is changed to adding 7 ml of concentrated hydrochloric acid, and adding 10 ml of deionized water is changed to adding 7 ml of deionized water. Other parameters and processes are the same as those in embodiment 1, and a three-dimensional TiO2-Ag / AgCl composite material is prepared, in which TiO2 nanoneedles form micron balls filling the gaps in the AgCl block. The SEM image of the three-dimensional TiO2-Ag / AgCl composite material is shown as follows: Figure 7 and Figure 8 As shown, the length of the TiO2 nanoneedle is about 0.4-0.8 μm, the diameter is about 5-20 nm, and the particle size of the Ag nanoparticles is about 5-40 nm. The process XRD diagram is shown in Fig. 9 As shown, the diffraction pattern shows typical diffraction peaks of rutile phase TiO2, cubic AgCl and Ag crystals, without any other impurity phase signals.

[0050] Sample analysis

[0051] The SERS activity and stability of the three-dimensional TiO2-Ag / AgCl composite material prepared in Example 1 were tested in an indoor light, temperature, and air environment;

[0052] The concentrations used were 10 -4 mol / L、10 -6 mol / L、10 -8 mol / L、10 -10 mol / L norfloxacin antibiotic solution was used as the test object; the three-dimensional TiO2-Ag / AgCl composite material prepared in the same batch was cut into 4 pieces and randomly numbered 1 to 4; 10 -4 mol / L、10 -6 mol / L、10 -8 mol / L、10 -10 mol / L norfloxacin solution, the volume of the solution added was 5 μL, and after natural drying under the same conditions, Raman spectroscopy was performed. The laser wavelength used in the test was 633 nm, the number of integrations was 3, and 20 points of each sample were randomly tested 20 times. The surface enhancement spectrum obtained after averaging is shown in the figure below. Fig.10 As shown. Fig.10 It can be seen that when the three-dimensional TiO2-Ag / AgCl composite material is used to detect norfloxacin solution, -4 ~10 -10 mol / L norfloxacin solution has high SERS detection activity. Another three-dimensional TiO2-Ag / AgCl composite material prepared in the same batch was cut into 10 pieces, randomly numbered 1 to 10, and stored in a glass container at room temperature, air atmosphere, and 50% humidity. One sample substrate was taken every day according to the number to test the newly configured 10 -6 The same Raman test was performed on mol / L norfloxacin solution. The laser wavelength used for the test was 633 nm, the number of integrations was 3, and 20 points of each sample were randomly tested 20 times. The average surface enhancement spectrum was as follows: Fig.11 As shown, the three-dimensional TiO2-Ag / AgCl composite material has a certain long-term SERS activity for norfloxacin solution. Accordingly, the three-dimensional TiO2-Ag / AgCl composite material prepared by the present invention can be used in the detection and identification fields of agricultural residues in water, food additives, environmental analysis, drug analysis, biochemistry, etc.

[0053] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a three-dimensional TiO2-Ag / AgCl composite material, characterized in that: The following steps are involved: (1) Add titanium isopropoxide to a mixture of ethylene glycol, concentrated hydrochloric acid and water, stir, immerse washed and dried Ag foil therein, and react at a temperature of 80 to 150° C. for 1.5 to 7.5 h to prepare a substrate Ag-based TiO2-AgCl; the thickness of the Ag foil is 0.005 to 2.0 mm, and the purity is 99.00% to 99.998%; (2) placing the Ag-based TiO2-AgCl substrate under a xenon lamp light source, controlling the light source current to irradiate the substrate, so that part of the AgCl component in the substrate undergoes photoreduction to generate active elemental Ag; (3) placing the substrate after the light treatment in a protective atmosphere, the protective atmosphere is a nitrogen atmosphere or a nitrogen-hydrogen mixed atmosphere, controlling the heating temperature to be 200 to 500° C., and the heating time to be 30 to 120 min, so that the active single substance Ag relies on the TiO2 monomer for thermal migration, and preparing a three-dimensional TiO2-Ag / AgCl composite material; In step (2), the wavelength of the xenon lamp light source is 300 nm ≤ λ ≤ 1100 nm, the xenon lamp light source exit window is 5.0 to 50 cm away from the substrate, and the light source current is controlled so that the irradiation intensity received by the substrate is 10.0 to 200 mW / cm 2 The irradiation time was controlled between 2.0 and 30 min.

2. The method for preparing the three-dimensional TiO2-Ag / AgCl composite material according to claim 1, characterized in that: In the mixed solution in step (1), the volume ratio of ethylene glycol, concentrated hydrochloric acid and water is 0.2-1:0.2-1:1; and the amount of titanium isopropoxide added is 1-5 v / v% based on the volume of water in the mixed solution.

3. A three-dimensional TiO2-Ag / AgCl composite material obtained according to the preparation method of the three-dimensional TiO2-Ag / AgCl composite material according to claim 1 or 2.

4. The three-dimensional TiO2-Ag / AgCl composite material according to claim 3, characterized in that: In the three-dimensional TiO2-Ag / AgCl composite material, TiO2 nanoneedles are in-situ assembled on an Ag foil substrate based on the inlay effect of AgCl, the TiO2 nanoneedles form a lawn-like three-dimensional structure, and Ag nanoparticles are randomly distributed on the TiO2 nanoneedles; the length of the TiO2 nanoneedles is 0.2 to 1 μm, the diameter is 10 to 60 nm, and the particle size of the Ag nanoparticles is 5 to 40 nm.

5. Use of the three-dimensional TiO2-Ag / AgCl composite material according to claim 3 or 4 in surface enhanced Raman scattering detection.

6. A method for detecting antibiotics in an aqueous solution, characterized in that: Use the three-dimensional TiO2-Ag / AgCl composite material described in claim 3 or 4.

7. The method for detecting antibiotics in an aqueous solution according to claim 6, characterized in that: The antibiotics are quinolone antibiotics, including norfloxacin, ofloxacin, ciprofloxacin or fleroxacin.

Citation Information

Patent Citations

  • Ag / TiO2 flexible SERS substrate capable of being repeatedly utilized and preparation method thereof

    CN105372223A

  • Surface-enhanced Raman scattering substrate and preparation method and application thereof

    CN113670893A

  • Preparation method for raman spectrum detection substrate

    CN108896530A

  • Precious metal modified titanium dioxide nanorod array with excellent surface enhanced Raman scattering property and preparation method and application of precious metal modified titanium dioxide nanorod array

    CN113267483A